BIOM-32. DNA METHYLATION SUBCLASSES PREDICT THE BENEFIT FROM GROSS TOTAL TUMOR RESECTION IN IDH-WILDTYPE GLIOBLASTOMA PATIENTS. (14th November 2022) - Drexler, Richard; Schüller, Ulrich; Eckhardt, Alicia; Filipski, Katharina; Hartung, Tabea; Harter, Patrick; Divé, Iris; Forster, Marie-therese; Czabanka, Marcus; Jelgersma, Claudius; Onken, Julia; Vajkoczy, Peter; et al.
Abstract: DNA methylation-based tumor classification allows an enhanced distinction into subgroups of glioblastoma. However, the clinical benefit of DNA methylation-based stratification of glioblastomas remains inconclusive. We performed a multicentric cohort study including 430 patients with newly diagnosed glioblastoma whose tumors were subjected to DNA methylation profiling. The primary outcome was overall survival (OS) and progression-free survival (PFS). Secondary outcomes were the prognostic relevance of EOR and MGMT promoter methylation status as well as surgical benefit for recurrent glioblastoma. After stratifying patients in accordance with their DNA methylation subclasses RTK I, RTK II, and mesenchymal (MES), outcome analyses revealed no significant differences between these three methylation subclasses ( p = 0.06). RTK I or RTK II tumors who underwent gross-total resection (GTR) or near GTR had a longer OS and PFS than partially resected patients ( p < 0.01). In the MES subclass, no survival benefit for a maximized EOR was found ( p = 0.33). In multivariate analysis, the therapy response-predictive value of MGMT promoter methylation was evident for RTK I ( p < 0.01) and RTK II ( p = 0.02) but failed to be an independent factor in the MES subclass ( p = 0.06). For local recurrence, re-resection conveyed a progression-to-overall survival (POS) benefit ( p < 0.01), which was evident in the RTK I ( p = 0.03) and RTK II ( p < 0.01) subclasses, but not in the MES subclass ( p = 0.33).This study demonstrates a survival benefit from maximized EOR at surgery for newly diagnosed and recurrent glioblastomas of the RTK I and RTK II subclass but not the MES subclass. Hence, it needs to be carefully considered whether the MES subclass should be treated with maximal surgical resection, especially when located in eloquent areas and at time of recurrence.